Protective effects of plant seed extracts against amyloid β-induced neurotoxicity in cultured hippocampal neurons - Okada, Yoshinori (Medknow Publications & Media Pvt Ltd, 2013)
AIM: Alzheimer's disease (AD) is characterized by large deposits of amyloid β (Aβ) peptide. Aβ is known to increase reactive oxygen species (ROS) production in neurons, leading to cell death. In this study, we screened 15 plant seeds’ aqueous extracts (PSAE) for inhibitory effects on Aβ (25-35)-induced cell death using hippocampus neurons (HIPN). MATERIALS AND METHODS: Fifteen chosen plants were nine medical herbs (Japanese honeywort, luffa, rapeseed, Chinese colza, potherb mustard, Japanese radish, bitter melon, red shiso, corn, and kaiware radish) and six general commercial plants (common bean, komatsuna, Qing geng cai, bell pepper, kale, and lettuce). PSAE were measured for total phenolic content (TPC) with the Folin–Ciocalteu method, and the 2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging effect of each seed extract was measured. To find a protectant against Aβ-induced oxidative stress, we screened 15 PSAE using a 2’, 7’-dichlorofluorescein diacetate assay. To further unravel the anti-inflammatory effects of PSAE on Aβ-induced inflammation, PSAE were added to HIPN. The neuroprotective effects of the PSAE were evaluated by Cell Counting Kit-8 assay, measuring the cell viability in Aβ-induced HIPN. RESULTS: TPC of 15 PSAE was in the range of 0.024-1.96 mg of chlorogenic acid equivalents/gram. The aqueous extracts showed antioxidant activities. Furthermore, intracellular ROS accumulation resulting from Aβ treatment was reduced when cells were treated with some PSAE. Kale, bitter melon, kaiware radish, red shiso, and corn inhibited tumor necrosis factor-alpha secretion by the Aβ-stimulated neurons and all samples except Japanese honeywort showed enhancement of cell survival. CONCLUSION: From these results, we suggest that some plant seed extracts offer protection against Aβ-mediated cell death.